2012
DOI: 10.1063/1.4759124
|View full text |Cite
|
Sign up to set email alerts
|

Hall effect measurements on InAs nanowires

Abstract: We have processed Hall contacts on InAs nanowires grown by molecular beam epitaxy using an electron beam lithography process with an extremely high alignment accuracy. The carrier concentrations determined from the Hall effect measurements on these nanowires are lower by a factor of about 4 in comparison with those measured by the common field-effect technique. The results are used to evaluate quantitatively the charging effect of the interface and surface states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
93
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(102 citation statements)
references
References 15 publications
7
93
1
1
Order By: Relevance
“…Using the sheet resistance Rs from the VDP measurements, the electron Hall mobility was obtained through l H ¼ 1 qR S n S resulting in l H ¼ 5400 cm 2 /V s. In comparison, a detailed study on Hall measurements on h111i oriented InAs NWs with diameters larger than 160 nm was recently reported. 19 These NWs contained a high density of stacking faults similar to the devices fabricated here, and exhibited a mobility of l H ¼ 3120 cm 2 /V s. An investigation of h110i oriented InAs NWs with diameters larger than 440 nm was reported by Cui et al 20 who found l H > 8000 cm 2 /V s, attributing the high mobility to the pure zinc-blende crystal structure. Measurements on planar, 50 lm wide and 20 nm thick InAs Hall structures with (100) surface orientation 21 resulted in l H ¼ 7000 cm 2 /V s while films affected by dislocations resulted in a significantly reduced mobility of l H $ 2000 cm 2 /V s. The comparatively high mobility value measured here for a thin InAs crossbar (95 Â 23 nm 2 ) which also includes stacking faults thus strongly suggests the absence of dislocations, as such defects clearly are most detrimental to the mobility.…”
supporting
confidence: 73%
“…Using the sheet resistance Rs from the VDP measurements, the electron Hall mobility was obtained through l H ¼ 1 qR S n S resulting in l H ¼ 5400 cm 2 /V s. In comparison, a detailed study on Hall measurements on h111i oriented InAs NWs with diameters larger than 160 nm was recently reported. 19 These NWs contained a high density of stacking faults similar to the devices fabricated here, and exhibited a mobility of l H ¼ 3120 cm 2 /V s. An investigation of h110i oriented InAs NWs with diameters larger than 440 nm was reported by Cui et al 20 who found l H > 8000 cm 2 /V s, attributing the high mobility to the pure zinc-blende crystal structure. Measurements on planar, 50 lm wide and 20 nm thick InAs Hall structures with (100) surface orientation 21 resulted in l H ¼ 7000 cm 2 /V s while films affected by dislocations resulted in a significantly reduced mobility of l H $ 2000 cm 2 /V s. The comparatively high mobility value measured here for a thin InAs crossbar (95 Â 23 nm 2 ) which also includes stacking faults thus strongly suggests the absence of dislocations, as such defects clearly are most detrimental to the mobility.…”
supporting
confidence: 73%
“…We observe no difference, within statistical error, between mobilities measured at 1 mV and 10 mV bias. Recently, challenging Hall effect measurements were carried out [35,36] on InAs nanowires showing that immobile interface charge accounts for an appreciable fraction of the the total gate-induced charge, meaning that field-effect measurements tend to underestimate the true mobility. We argue that this mechanism would most strongly affect the mobility estimates in the device "on" state rather than at peak mobility where the surface potential is nearly flat.…”
Section: Resultsmentioning
confidence: 99%
“…This estimation is close to the observed diameter of 100 nm. Hall effect measurements have already been reported in InP core-shell NW by Storm et al [48] and in InAs NW by Blömers et al [49] using local probes on devices with widths around 200 nm. In contrast, the result presented here is evidence of the QHE regime in a NW, highlighting the specific transport properties under high magnetic field.…”
Section: Magnetotransport Through Ballistic Edge Statesmentioning
confidence: 84%